OVERVIEW OF THE QUALITY OF LIFE OF POST-CATARACT PATIENTS AT THE SAMBALIUNG HEALTH CENTER - Dewi Darmala Sari (Journal of Health, Sport, and Nursing, 2026)
Background: Cataracts are a leading cause of global blindness that has a wide impact on the lives of sufferers. Cataract surgery is the main solution for restoring vision, but its success needs to be studied through post-action quality of life measurements. This study aims to describe the quality of life of patients after cataract surgery in the work area of the Sambaliung Health Center in 2025. Methods: This descriptive quantitative study with a cross-sectional design was carried out in December 2025. All post-cataract surgery patients in the work area of the Sambaliung Health Center were sampled (n = 37) through total sampling. Data were collected using the Indonesian version of NEI VFQ-25 which has been validated (Cronbach's α = 0.961). Quality of life was categorized as Good (≥75), Adequate (60–74), and Poor (<60), analyzed univariately using SPSS. Results: The majority of respondents were late elderly (56–65 years, 45.9%), female (51.4%), high school educated (32.4%), and self-employed (32.4%). A total of 28 respondents (75.7%) had a good quality of life, 6 respondents (16.2%) were adequate, and 3 respondents (8.1%) were poor. Perfect scores were achieved on the dependency and color vision subscales (100%), while social function and role difficulties recorded the highest proportion of poor quality of life (27.0% each). Conclusion: Cataract surgery has a real positive impact on most dimensions of patients' quality of life in primary health care. However, the psychosocial aspect especially social function and role difficulties still require special attention. Holistic nursing care, including patient education and family support, is essential to optimize comprehensive recovery after cataract surgery.